Project Based learning to Improve Students’ Creativity In Speaking and Vocabulary Achievements - Agustiawati, Hartini (Enrich: Jurnal Pendidikan, Bahasa, Sastra dan Linguistik, 2022)
The purposes of this study were to find out (1) whether there was a significant difference in vocabulary achievement between students who were taught through Project Based Learning, , (2) whether there was a significant difference in speaking achievement between the students who were taught through project based learning, (3) whether there was a significant correlation between vocabulary and speaking achievements of the seventh grade students of Junior High school Number 18. The population of this study consisted of the seventh grade of Junior high school students. The total number of the population was 14, while the sample consisted of 14 students in the experimental group. In collecting the data, the pretest, treatment and posttest were used. However, the data were analyzed by using t-test. It was found that (1) there was a significant difference in vocabulary achievement where the sig value (2 tailed) was lower than 0.05, (2) there was a significant difference in speaking achievement where the sig value (2 tailed) was lower than 0.05, (3) there was a significant correlation and contribution between vocabulary and speaking. It could be concluded that Project based Learning can improved students’ vocabulary and speaking achievements.